Legal protection of intellectual property objects – a condition for their successful commercialization - Schimpf, Karin; Pererva, P. G. (ТОВ "Юридична компания "Юрсервіс", 2022)
For the commercialization of each intellectual property object, the most suitable legal protection regimes are extremely important. The rights to all objects are registered, deposited, patented, if necessary, a trade secret regime (know-how, production secrets) is introduced. The ways of commercialization of intellectual property that can maximize the profit of the company are determined.
Правова охорона об'єктів інтелектуальної власності - умова їх успішної комерціалізації
Keywords: intellectual property; law; commercialization; technology transfer; economic efficiency; industrial enterprises